Ceramic interfaces 2 - Yoo, H. I. 1951-; Kang, S.-J. L. (IOM Communications, 2001)
This volume contains the proceedings of the 4th International Workshop on Ceramic Interfaces held at the Korea Advanced Institute of Science and Technology, Taejon, Korea. 27 specialists from 8 countries contributed to the workshop which was divided into 3 sessions: Microstructural Development; Transport; Interfacial Phenomena and Kinetics.
Keywords: Ceramic materials -- Surfaces -- Congresses.; elektronické knihy; electronic books